A Systematic Procedure for Case Study Research in Biophilic Design: Toward Contextual and Regenerative Inquiry - Pande Putu Dwi Novigga Artha; Indah Widiastuti; Dewi Larasati (Talenta Publisher, 2025)
Biophilic Design is an architectural approach that seeks to restore and strengthen the human connection with nature as a means to enhance the physical and psychological well-being of building occupants. Over the past two decades, this concept has gained substantial attention across academic disciplines and professional practices worldwide. However, despite its growing prominence, there remains a lack of structured research methodologies that systematically explore the application of Biophilic Design principles across diverse architectural contexts. This study addresses that gap by proposing a systematic protocol for conducting case study research grounded in the theoretical framework of Biophilic Design. The aim is to provide clear and replicable methodological guidance for investigating how nature-based design strategies can support contextual and regenerative practices in architecture, including but not limited to vernacular or traditional environments. The research method employed is a Systematic Literature Review (SLR) of peer-reviewed publications from reputable databases including Scopus, Web of Science (ESCI), and DOAJ, focusing on studies published between 2019 and 2024. Based on the synthesis of the selected literature, the study formulates a seven-stage protocol for case study research. These stages include case selection, data collection techniques such as field observation and in-depth interviews, and thematic analysis for qualitative data interpretation. The findings highlight the necessity of involving key stakeholders—such as cultural experts, historians, and anthropologists—throughout the research process to ensure accurate interpretation of local ecological and cultural values. This protocol is expected to serve as a methodological reference for researchers and practitioners seeking to implement Biophilic Design in a way that is context-sensitive, socially and ecologically regenerative, and rooted in local wisdom.